PROBLEMATIKA PEMENUHAN HAK-HAK NARAPIDANA TERKAIT OVERKAPASITAS DI DALAM LEMBAGA PEMASYARAKATAN DI INDONESIA - Nurul Syahvira; Davit Rahmadan; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
As one of the sub-systems of criminal justice, penitentiary institutions (Lapas) have a rolein implementing the guidance of prisoners and correctional students through a correctionalsystem based on education, rehabilitation and reintegration. However, in its development, thecoaching that was carried out was not optimal because of the complexity of the problems thatoccur in prisons. One of the root causes of problems in correctional institutions/detention centersis over capacity. Various policies have been taken to overcome the problem of over capacity,including through the rehabilitation of buildings to the construction of new buildings with the aimof increasing the capacity of prisons and detention centers. However, this policy was notsignificantly able to overcome the problem of overcapacity considering that the additionalnumber of prisoners and inmates was still far greater as a result of the high crime rate in society.This study was structured using qualitative analysis. Qualitative analysis producesdescriptive data, namely collecting all the necessary data obtained from primary and secondarylegal materials. This type of research is normative juridical, namely research that is focused onexamining the application of rules or norms in positive law.The results of the research conducted by the author are, first, the problem of fulfilling therights of convicts related to overcapacity in correctional institutions in Indonesia, namelyconvicts not getting proper resting places due to limited space, overcapacity in prisons alsocauses other crimes, such as riots in correctional institutions, less optimal coaching carried outby correctional officers; Health problems; and satisfaction of the conjugal visit. Second, theideal form of granting and fulfilling the rights of convicts in correctional institutions in Indonesia,such as granting remissions, assimilation, conditional leave, leave to visit family, leave beforerelease; Application of Rehabilitation; Application of restorative justice; Relocation of convictsand construction of new land; Optimizing coaching; and good time allowance developmentprogram. The author's suggestion is that for the government this condition depends ongovernment policies to regulate existing laws and regulations and strengthen coaching programsto accelerate the reintegration of convicts; Law enforcers should prioritize the restorative justiceapproach in cases of minor crimes that harm other people or carry out rehabilitation for narcoticsabuse cases (except for recidivists).Keywords: Fulfillment, Convict Rights, Penitentiary, Overcapacity